Evaluación del efecto de milbemicina oxima e ivermectina en perros (Canis familiaris) positivos a microfilariasis en zonas rurales - Mateus Intriago, Nayely Jamileth (2023)
The main function of the study was to combat Microfilariae in positive dogs from rural areas. The evaluation of the effect of Milbemycin Oxime and Ivermectin in canines allowed us to analyze the effectiveness of these drugs and determine which of them performs the best function. The methodology used in this assessment was the statistical bibliographic method and the inductive and intuitive method; and techniques such as observation through the WOO test, being a conventional examination, where microfilariae are observed. For this investigation, 30 positive canines were selected, 3ml of blood was taken from each individual to assess their hemoparasite load. All positive patients in the sampling from day one were given orally two treatments T1 Milbemycin Oxime and T2 Ivermectin. This process was carried out on four occasions to observe its evolution, and were completed on day one, four, 14 and 29. It is important to mention that the Chi x2 technique was used, which made a comparison between the identified variables that allowed us to know the degree of influence that these have within the object of study; and significant differences were found in favor of the effect of Milbemycin Oxime on Dirofilaria on day 14 with p value <0.0324 and on day 29 p value <0.0443. Treatment with Ivermectin had lower efficacy and there were no significant differences.